1975
DOI: 10.3177/jnsv.21.49
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of cytidine diphosphate choline and its changes in the digestive tract.

Abstract: Intestinal absorption of cytidine diphosphate choline (CDP choline), its structural changes in the digestive tract, and hepatic uptake have been investigated in rats using 14C-labeled (14CH3 attached to N of choline) and 3H-labeled (at C5 of pyrimidine) compounds. The results indicate that: 1) CDP-choline is relatively stable in the stomach, but is quickly degraded into cytidine and choline in the intestine; 2) The hepatic uptakes of 14C and 3H reach the maximum in two to three hours after oral administration;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Yashima et al [65] used citicoline doubly-labelled with carbon-14 at the methyl groups of choline and tritium at C5 of pyrimidine, and obtained evidence of CDP-choline being broken down in the intestine, resulting in release of choline and cytidine, likely due to the actions of intestinal esterases and pyrophosphatases. However, the authors concluded that “these split compounds as well as the original CDP-choline may be absorbed from the intestinal mucosa as such”.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…Yashima et al [65] used citicoline doubly-labelled with carbon-14 at the methyl groups of choline and tritium at C5 of pyrimidine, and obtained evidence of CDP-choline being broken down in the intestine, resulting in release of choline and cytidine, likely due to the actions of intestinal esterases and pyrophosphatases. However, the authors concluded that “these split compounds as well as the original CDP-choline may be absorbed from the intestinal mucosa as such”.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…Cytidine 5'-diphosphocholine (CDP-choline) has been widely used for the treatment of different diseases of the central nervous system (Manaka et al, 1974;Salvadorini et al, 1975;Cohadon et al, 1982;Lecuire & Duplay, 1982). Membrane diffusion of this compound, after intravenous or oral administration, requires splitting of the molecule into CMP and phosphocholine, which are later metabolized to cytidine and choline (Yashima et al, 1975;Lopez-G. Coviella et al, 1987). These two major circulating products are then incorporated into their respective cellular pools and their increased concentrations would account for the pharmacological properties of CDP-choline.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane diffusion of this compound, after intravenous or oral administration, requires splitting of the molecule into CMP and phosphocholine, which are later metabolized to cytidine and choline (Yashima et al, 1975;Lopez-G. Coviella et al, 1987). These two major circulating products are then incorporated into their respective cellular pools and their increased concentrations would account for the pharmacological properties of CDP-choline.…”
Section: Introductionmentioning
confidence: 99%